Melihat Peluang dan Manfaat Kerjasama Perjanjian Perdagangan Bebas Indonesia-EFTA dalam Sektor Pertanian - Melkis, Juan Carlos (TRANSBORDERS: International Relations Journal, 2024)
This research utilizes a qualitative method to gain in-depth insights into the impact of the European Free Trade Association (EFTA) on the agricultural sector in Indonesia. The primary focus of the study is to examine the extent of the impact of this agreement by examining the regulatory changes implemented by Indonesia and the positive contributions observed in the agreement. It is evident that IE-CEPA provides positive support to Indonesia's agricultural sector by enhancing market access, diversifying products, and supporting flagship commodities. However, it is crucial to continue monitoring the impact of this agreement on farmers' well-being and the long-term sustainability of the agricultural sector. The implementation of this agreement has the potential to reduce tariff barriers by up to USD 1.35 billion, reflecting significant opportunities for Indonesia's economic growth through expanded exports and investments in the agricultural sector.